Autogenic allotopic small-bowel mucosa transplantation in beagles: a new perspective for treatment of small-bowel syndrome? - Zachariou, Zacharias; Daum, Roland; Beiler, Hans Albert; Gorgas, Karin (European journal of pediatric surgery, 1998)
Thieme E-Books & E-Journals
Elektronische Reproduktion der Druck-Ausgabe 25. März 2008
Zusammenfassung in englischer, französischer und spanischer Sprache
Gesehen am 10.09.2024